PROFILE OF PREGNANT WOMEN WITH HEPATITIS B IN SURABAYA 2020-2023 - Langgeng Fatilatu Ummah; Atika , Atika; Dwilda, Euvanggelia; Andriyanti, Andriyanti (UNIVERSITAS AIRLANGGA, 2025)
Background: Hepatitis B virus (HBV) infection is a major public health issue. Worldwide, approximately 2 billion people have been infected, and more than 240 million are chronic carriers at risk of progressive liver diseases such as cirrhosis, liver failure, and hepatocellular carcinoma (HCC) (WHO, 2015). Method: This research method is descriptive with sampling techniques using random sampling that meets the inclusion criteria of 187 samples. The data collection was conducted using secondary data from the SIHEPI application for the years 2020-2023 at the Health Office of Surabaya City. Result: The frequency characteristics were obtained from 187 pregnant women with ages between 20-35 years (70.6%) who were in the third trimester of pregnancy (41.7%) and the majority of mothers were unemployed (58.3%). Most babies born to mothers with hepatitis B received HBIG (95.7%), but one baby was infected with hepatitis B (0.5%) Conclusion : The majority of babies born to mothers with hepatitis B have received HBIG, and 77.0% of babies were not infected.